2016
DOI: 10.24059/olj.v20i4.1054
|View full text |Cite
|
Sign up to set email alerts
|

Online Teacher Work to Support Self-Regulation of Learning in Students with Disabilities at a Fully Online State Virtual School

Abstract: Students with disabilities represent a growing number of learners receiving education in K-12 fully online learning programs. They are, unfortunately, also a large segment of the online learning population who are not experiencing success in these environments. In response, scholars have recommended increasing instruction in self-regulation skills for these students, but whether teachers are able to promote self-regulation as part of their instruction and how they will do so remains unknown. The purpose of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 12 publications
1
32
0
8
Order By: Relevance
“…We recommend that online programs provide a parent portal with a dashboard that clearly communicates important student performance and progress information. While previous researchers have described or advocated for similar dashboards for teachers (Borup, Graham, & Drysdale, 2014;Adams Becker, Freeman, Giesinger Hall, Cummins, & Yuhnke, 2016;Dickson, 2005;Rice & Carter, 2016;Zhang & Almeroth, 2010) and students (Patrick, Kennedy, & Powell, 2013), additional attention needs to be paid to parent dashboards. While teacher dashboards are becoming more common, they can be ignored when poorly designed (Murphy et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…We recommend that online programs provide a parent portal with a dashboard that clearly communicates important student performance and progress information. While previous researchers have described or advocated for similar dashboards for teachers (Borup, Graham, & Drysdale, 2014;Adams Becker, Freeman, Giesinger Hall, Cummins, & Yuhnke, 2016;Dickson, 2005;Rice & Carter, 2016;Zhang & Almeroth, 2010) and students (Patrick, Kennedy, & Powell, 2013), additional attention needs to be paid to parent dashboards. While teacher dashboards are becoming more common, they can be ignored when poorly designed (Murphy et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Research has found K-12 online teachers can provide a high degree of support that builds close, caring relationships with some students (Velasquez, Graham, & Osguthorpe, 2013). However, supplemental courses rely heavily (if not exclusively) on asynchronous communication, making it difficult for online teachers to provide all of their students with the timely support they require (Rice & Carter, 2016). As a result, online students are increasingly being provided with an on-site facilitator who works with them in their local brick-and-mortar schools.…”
mentioning
confidence: 99%
“…Μεταξύ των μαθητών υπήρξαν αρκετοί που ζούσαν σε αγροτικές αλλά και απομονωμένες περιοχές των Η.Π.Α., του Καναδά και άλλων χωρών (Hannum,et al,2009;De la Varre et al,2010;Hiew et al, 2010;Barbour,2011;Holian et al,2014;De la Varre, 2014 ). Τρεις έρευνες είχαν ως δείγμα παιδιά με ειδικές ανάγκες (Burdette et al, 2013;Burdette et al, 2014;Johnston,2014;Rice et al, 2016 Thomson,2010;Wallace,2009). Φυσικά δε συμμετείχαν μόνο οι μαθητές στις έρευνες αλλά σε αρκετές έλαβαν μέρος οι εκπαιδευτικοί, οι διευθυντές των σχολείων τους καθώς και οι γονείς τους.…”
Section: παρουσίαση αποτελεσμάτωνunclassified
“…Φυσικά δε συμμετείχαν μόνο οι μαθητές στις έρευνες αλλά σε αρκετές έλαβαν μέρος οι εκπαιδευτικοί, οι διευθυντές των σχολείων τους καθώς και οι γονείς τους. Συμμετείχαν εκπαιδευτικοί με διδακτική εμπειρία και επιμόρφωση στην εξ αποστάσεως διδασκαλία, διευθυντές σχολείων που εφαρμόζουν προγράμματα εξ αποστάσεως (συμπληρωματικής, μικτής, ηλεκτρονικής μάθησης), στελέχη της εκπαίδευσης, διευθυντές σχολείων, διευθυντές εκπαίδευσης, σχολικοί σύμβουλοι όπως μεταξύ άλλων στις έρευνες των (Ulker et al, 2013;Rice et al, 2016;Archambault et al, 2009;Reid et al, 2009;Hannum,et al,2009;Holian et al2014;Barbour,2016 ), αλλά σε αρκετές έρευνες και οι γονείς των μαθητών (Ulker et al, 2013;Burdette et al, 2014;Johnston,2014;Siko, 2014) μια και λειτουργούν και αυτοί ως επιβλέποντες.…”
Section: παρουσίαση αποτελεσμάτωνunclassified
See 1 more Smart Citation